2019
DOI: 10.7567/1882-0786/ab3ab7
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-selective asymmetric transmission via the lossy acoustic metasurface

Abstract: Asymmetric acoustic transmission (AAT) has been demonstrated using diverse acoustic metasurfaces (AMs). Here, we show that an emerging class of lossy AMs enables frequency-selective AAT. The asymmetric and symmetric transmissions can be realized at interested operating frequencies in specific incident angle ranges. The underlying mechanism is attributed to the inherent loss inside the labyrinthine structure of different arrangements. Our design introduces the freedom degree of frequency control for the achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Almeida et al, 2021). By properly designing the inner structures of metasurfaces, a great deal of fascinating features has been realized, such as anomalous reflection and refraction (Liu et al, 2017;Li et al, 2018;Liu and Jiang, 2018;Qian et al, 2019;Su and Liu, 2020), asymmetric propagation (Shen et al, 2016;Li et al, 2017;Song et al, 2019), orbital angular momentum (Shi et al, 2019;Gao et al, 2021;Hou et al, 2021), near-perfect absorption (Zhu et al, 2019;Kumar and Lee, 2020;Donda et al, 2021;Liu et al, 2021a), beam focusing (Ma et al, 2018;Liu et al, 2021b;Xie and Hou, 2021), self-bending beams (Li and Assouar, 2015), acoustic cloaking (Jin et al, 2019;Li et al, 2019;Zhao et al, 2019;Fan et al, 2020;Zhou et al, 2021), and convolution operation and addition operation (Cao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Almeida et al, 2021). By properly designing the inner structures of metasurfaces, a great deal of fascinating features has been realized, such as anomalous reflection and refraction (Liu et al, 2017;Li et al, 2018;Liu and Jiang, 2018;Qian et al, 2019;Su and Liu, 2020), asymmetric propagation (Shen et al, 2016;Li et al, 2017;Song et al, 2019), orbital angular momentum (Shi et al, 2019;Gao et al, 2021;Hou et al, 2021), near-perfect absorption (Zhu et al, 2019;Kumar and Lee, 2020;Donda et al, 2021;Liu et al, 2021a), beam focusing (Ma et al, 2018;Liu et al, 2021b;Xie and Hou, 2021), self-bending beams (Li and Assouar, 2015), acoustic cloaking (Jin et al, 2019;Li et al, 2019;Zhao et al, 2019;Fan et al, 2020;Zhou et al, 2021), and convolution operation and addition operation (Cao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, the repaid development of coding and programmable metamaterials and metasurfaces has provided a flexible method to achieve the frequency-tunable wavefront modulation in electromagnetics, which has been witnessed in the past few years [25,26]. Inspired by these concepts, analogous coding acoustic metasurfaces have also occurred [27][28][29][30][31][32][33]. Xie et al [27] have designed two resonant elements with a phase difference of π to stand for the bits of '0' and '1', respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al [27] have designed two resonant elements with a phase difference of π to stand for the bits of '0' and '1', respectively. Song et al [28] have employed four diverse labyrinth structures to compose the 2 bit binary acoustic metasurfaces to modulate the transmitted wavefronts at two different frequencies. Xia et al [24] have reported a programmable ATI based on two digital elements '0' or '1', which consist of honeycomb-lattice SCs made of cylindrical rods with different diameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the first strategy, the systems with the nonlinear effect, [1][2][3][4] the circulating fluid, [5][6][7][8][9] the time-dependent properties [10][11][12][13] have been proposed. Based on the second strategy, versatile design proposals have been conducted to realize the asymmetric acoustic transmission, such as combining the zero-index metasurface with the gradient index metasurface [14][15][16] or with the binary metasurface, 17) using dual-layer gradient index metasurfaces, 18,19) using the integer-parity feature of acoustic metasurfaces, 20,21) using acoustic metagrating containing iron cylinders only assisted with a genetic algorithm optimization, 22) using coded metasurfaces, 23) using modeselective resonant materials, 24) using the lossy gradient index metasurface [25][26][27] and using a high-index prism. 28) In addition, the asymmetric acoustic transmission in a straight open tunnel has also been conducted, which may be highly desirable in the design of vent ducts or anti-noise windows.…”
mentioning
confidence: 99%